METASTATIC THYMOMA OF THE BREAST : CASE REPORT - Salvador, Anna Dias; Alves, Gabriela Ramos; Lima, Enaldo Melo; Ricardo, Bernardo Ferreira Paula; Silva, Henrique Moraes Salvador (Mastology, 2021)
Introduction: Thymomas are rare malignant epithelial neoplasms arising in the thymus. These tumors are commonly located in the prevascular mediastinum but can also be found in other regions of the mediastinum, neck, pulmonary hilum, thyroid gland, lungs, pleura, or pericardium. This disease could be suspected as an incidental finding identified on imag-ing, local thoracic symptoms or due to a paraneoplastic syndrome. Pleural or pericardial effusions are the most common manifestations of more disseminated disease and may also cause thoracic symptoms. Extrathoracic metastases are seen in fewer than seven percent of patients at presentation, most commonly in the kidneys, extrathoracic lymph nodes, liver, brain, adrenals, thyroid, and bone. Case report: A 66-year-old, white female patient, with previous left mastectomy due to a phyllodes sarcoma in 1997. Diagnosed with malignant thymoma in 2013 and pleural involvement, undergoing systemic chemotherapy and surgery with complete remission of the disease at that time. Two years after, in 2015, presented with disease recurrence in the diaphragm, pleura and lymph nodes, undergoing new surgery, radiotherapy and a second line chemotherapy regimen. Over the years, the disease progressed despite the cancer treatment instituted. In December 2020, the patient presented nodulation in the right breast, with core biopsy suspicion of ductal carcinoma. Undergoing quadran-tectomy with lymph node biopsy, with the surgical pathological report finding of thymoma metastasis, resected with free margins. The patient is currently at the 31st pembrolizumab cycle, in good clinical condition